Model Integratif Kepastian Hukum, Tata Kelola Manajemen, dan Ketahanan Ekonomi dalam Membangun Organisasi yang Berkelanjutan: (Sebuah Pendekatan Interdisipliner) - Rehulina Bangun; Sulaiman Ahmad; Syahrudin Marpaung; Cahyoginarti Cahyoginarti; Ratna Ratna (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to develop an Integrative Model of Legal Certainty, Management Governance, and Economic Resilience in building sustainable organizations through an interdisciplinary approach that combines legal, management, and economic perspectives. This research employs a qualitative approach using the Systematic Literature Review method, supported by library research and conceptual analysis. The literature review process was conducted systematically based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines by analyzing reputable scientific articles, reference books, and relevant policy documents. The findings indicate that legal certainty serves as an institutional foundation that provides stability, legitimacy, and predictability in organizational operations. Meanwhile, management governance functions as an implementation mechanism that transforms regulations into transparent, accountable, responsible, independent, and equitable organizational practices. The integration of legal certainty and governance strengthens economic resilience by improving organizational capacity in managing risks, responding to strategic environmental changes, and maintaining long-term operational sustainability. This study identifies a research gap in previous studies, which often examine legal, governance, and economic dimensions separately, resulting in limited comprehensive frameworks. The theoretical contribution of this research is the development of an integrative model that combines Legal Certainty Theory, Good Corporate Governance Theory, Institutional Theory, Stakeholder Theory, Economic Resilience Theory, and Sustainable Organization Theory. The proposed model provides a conceptual foundation for academics, policymakers, and organizational leaders in developing governance strategies that enhance economic resilience and support sustainable organizational development amid global challenges.